Performance and environmental implication assessments of green bio-composite from rice straw and bamboo. (15th November 2022) - Pang, Bo; Zhou, Tong; Cao, Xue-Fei; Zhao, Bao-Cheng; Sun, Zhuohua; Liu, Xi; Chen, Yue-Ying; Yuan, Tong-Qi
Abstract: The clean and eco-efficient utilization of agro-industrial lignocellulose wastes is imperative for social development. This study proposes a viable strategy combining rice straw and waste bamboo particles into bio-composites using green adhesives. These new bio-composites can displace the traditional wood-particle boards, which is a viable strategy to economize on wood resources. The internal bonding strength reached 0.57 MPa, and the thickness swelling rate was 7 .00% (24h), which met the ISO requirements for P-FN MR1 particleboard in humid conditions. The characterizations of profile density distribution and microstructure were used to elucidate the mechanical strength and water resistance of bio-composites associated with the surface morphology of biomass and the density variation of bio-composites. The obtained green bio-composites can be utilized with long service life to realize carbon sequestration from agro-industrial lignocellulose wastes. According to the LCA, the net carbon flux could reach −1198.49 kg CO2 eq. when producing 1 m 3 bio-composite. Meanwhile, if this strategy is successfully extended to the global particleboard market, the utilization of 23.97 million tonnes of rice straw per year can economize on 1.61 million hm 2 of the forest, and decrease the emission of CO2 by 63.76 million tonnes. This study provided a new straw/bamboo-based bio-composite. While using agro-industrial lignocellulose wastes efficiently, this new strategy can appreciably favour carbon neutrality. Graphical abstract: Image 1 Highlights: Rice straw and waste bamboo particles were used to prepare bio-composites. The bio-composites possess strong mechanical strength and water resistance. The formaldehyde and 72 h TVOCs emissions were extremely low. The net carbon flux reached −1198.49 kg CO2 eq. when producing 1 m 3 bio-composite. This strategy can decrease the emission of CO2 63.76 million tonnes per year.